The Influence of Islamic Celebrity Endorser, Islamic Brand Image and Product Quality through Price as Moderating Variable on The Purchase Decision of Wardah Cosmetic Products - Darmawati Darmawati; Kanthi Arum; Irma Yuliani (CV. Ulil Albab Corp, 2025)
The emergence of the statement